PENGAWASAN, KESADARAN RETRIBUSI SERTA SARANA DAN PRASARANA SEBAGAI PENYEBAB TIDAK TERCAPAINYA TARGET PENERIMAAN RETRIBUSI PELAYANAN SAMPAH DI KABUPATEN LOMBOK BARAT - Yuli Astini; Rusdi Rusdi; RA Hannah Syabaneva (Jurnal Aplikasi Akuntansi, 2017)
The average earning of garbage disposal service retribution by West Lombok Regency's Office of City Planning, Gardening and Sanitation during the period of 2010-2014 was only 40% of the target in amount. This lower level of earning had prevented the Office from providing optimum services and caused it to be dependent on the Regency Government's subsidies. Ten employees of the Office and one retribution payer were selected as interviewees/informants through a purposive sampling technique, and the data taken from the interviews and from other documents were analyzed in a series of data reduction, display, and verification. The conclusion of this study provides an illustration on how the failure to achieve the targeted amount of revenue was caused by the lack of control in the part of the supervising levy collectors, the low awareness in the part of the community that prevented them from participating in the garbage disposal management and paying the retribution, and the inadequate availability of supporting infrastructure and facilities vis-a-vis the huge amount of garbage dumped every day by the city's population.